2014
DOI: 10.1007/s12576-014-0321-z
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-induced expression of peroxisome proliferator-activated receptor γ coactivator-1α isoforms in skeletal muscle of endurance-trained males

Abstract: The aim of the present study was to investigate the effect of acute aerobic exercise on the expression of PGC-1α transcript variants in human skeletal muscle. Seven endurance-trained athletes performed a 90-min cycling test (62% of VO2max). At resting state, the levels of N-truncated (NT)-PGC-1α and PGC-1α exon 1a-derived transcripts were significantly higher (>20-fold; P<0.05) than those of PGC-1α exon 1b- and 1c-derived transcripts. Acute exercise did not change the PGC-1α exon 1a-derived expression level, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
21
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 25 publications
7
21
1
1
Order By: Relevance
“…Exon 1c-derived mRNA was not detected in the post-exercise period. This observation is in agreement with our previous qPCR study, which showed very low post-exercise expression level of the exon 1c-derived PGC-1a mRNA in human skeletal muscle (Popov et al 2014). No other transcription start sites were found ( Fig.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Exon 1c-derived mRNA was not detected in the post-exercise period. This observation is in agreement with our previous qPCR study, which showed very low post-exercise expression level of the exon 1c-derived PGC-1a mRNA in human skeletal muscle (Popov et al 2014). No other transcription start sites were found ( Fig.…”
Section: Resultssupporting
confidence: 93%
“…AMP-activated protein kinase (AMPK), p38 mitogen-activated protein kinase (p38 MAPK), and Ca 2C /calmodulin-dependent protein kinase (CaMKII) appear to be important for regulation of activityinduced PGC-1a gene expression from the canonical promoter . Several groups (Norrbom et al 2011, Ydfors et al 2013, Popov et al 2014 have shown that in human skeletal muscle, acute exercise induces PGC-1a gene expression, mainly via the alternative promoter. Based on studies in rodent skeletal muscle, it was proposed that activation of exercise-induced expression via the alternative promoter is regulated by the beta-2 adrenergic receptor-protein kinase A (PKA)-cAMP response element-binding protein (CREB1) signalling pathway (Chinsomboon et al 2009, Tadaishi et al 2011.…”
Section: Introductionmentioning
confidence: 99%
“…The forward and reverse primers used in our study were directed to exon 2, which is common for all PGC 1α mRNA iso forms; i.e., expression from both of the PGC 1α pro moters was assessed. An increase in total expression of the PGC 1α gene after exercise seems to be mostly associated with the alternative promoter, which agrees with the results of our previous study [26]. Unexpect edly, an increase in exercise duration from 60 to 90 min did not increase PGC 1α gene expression, provid ing indirect evidence that the duration of moderate intensity exercise has no effect on expression of the PGC 1α gene.…”
Section: Discussionsupporting
confidence: 91%
“…IL-6 has been reported to further enhance AMPK activation in this case [17]. AMPK is the PGC-1a activation signaling factor, so the activated PGC-1a plays a role in the increase of mitochondrial biogenesis and angiogenesis, fiber type switching, fat oxidation in skeletal muscle and activation of muscle in atrophy prevention [1,27,32]. However, in this study, AMPK activity and PGC-1a protein expression significantly increased in both young rats and middle-aged rats after 8 weeks of ladder-climbing exercise, but there was no difference in age.…”
Section: Discussionmentioning
confidence: 92%